Association of blood lead and mercury with estimated GFR in herbalists after the ban of herbs containing aristolochic acids in Taiwan. Issue 8 (23rd May 2013) - Lin, Hsing-Hua; Chou, Shan-An; Yang, Hsiao-Yu; Hwang, Yaw-Huei; Kuo, Ching-Hua; Kao, Tze-Wah; Lo, Tsai-Chang; Chen, Pau-Chung
Abstract : Objective: This study was undertaken to explore the association of estimated glomerular filtration rate (GFR) with exposure to aristolochic acids (ALAs) and nephrotoxic metals in herbalists after the ban of herbs containing ALAs in Taiwan. Methods: This cross-sectional study recruited a total of 138 herbalists without end-stage renal disease or urothelial carcinoma from the Occupational Union of Chinese Herbalists in Taiwan in 2007. Aristolochic acid I (ALA-I) was measured by ultra-high-pressure liquid chromatography/ tandem mass spectrometry (UHPLC-MS/MS) and heavy metals in blood samples were analysed by Agilent 7500C inductively coupled plasma-mass spectrometry. Renal function was assessed by using a simplified Modification of Diet in Renal Disease Study equation to estimate GFR. Results: Blood lead was higher in herbal dispensing procedures (p=0.053) and in subjects who self-prescribe herbal medicine (p=0.057); mercury was also higher in subjects living in the workplace (p=0.03). Lower estimated GFR was significantly associated with lead (β=−10.66, 95% CI −18.7 to −2.6) and mercury (β=−12.52, 95% CI −24.3 to −0.8) with a significant interaction (p=0.01) between mercury and lead; however, estimated GFR was not significantly associated with high ALA-I level groups, arsenic and cadmium after adjusting for other confounding factors. Conclusions: We found that lower estimated GFR was associated with blood lead and mercury in herbalists after the ban of herbs containing ALAs in Taiwan. The ALA-I exposure did not show a significant negative association of estimated GFR, which might due to herbalists having known how to distinguish ALA herbs after the banning policy. Rigorous monitoring is still needed to protect herbalists and the general population who take herbs.